Effect of Radiotherapy and Low-Level Laser Therapy on Circulating Blood Cells of Rats: LLLT and Radiotherapy on Circulating Blood Cells - de Oliveira, Milene Castilhos; Krueger, Gabriel Francisco; Sganzerla, Juliana Tomaz; Gassen, Humberto Thomazi; Hernández, Pedro Antonio González; Allgayer, Mariangela da Costa; Miguens-Jr, Sergio Augusto Quevedo (Journal of Lasers in Medical Sciences, 2021)
Introduction: This study aimed to investigate the effect of low-level laser therapy (LLLT) on the blood cell count when applied to parotid glands of rats irradiated by volumetric modular arc therapy (VMAT). Methods: Thirty-two adult male Wistar rats were used in this study. Samples were randomly assigned to three groups: control group (CG, n = 8), immediate laser group (24 hours) (ILG, n=12), and late laser group (120 hours) (LLG, n=12). The two laser groups were previously subjected to VMAT radiotherapy in a single dose of 12 Gy. LLLT with an AsGaAl laser (660 nm, 100 mW) was applied at three points in the region of the parotid glands, right side, with the energy of 2 J per point (20s, 70 J/cm2) and a spot size of 0.0028 cm2 for 10 consecutive days. In euthanasia, blood samples were obtained by cardiac puncture. The samples from each group were processed by an automatic method and analyzed for erythrogram, leukogram, and platelet count values. The data were analyzed by ANOVA and each LLLT time point was analyzed in relation to the control group, with a significance level less than 0.05. Results: Groups using LLLT had higher red blood cell counts, being higher in the LLG (p = 0.000). The hematimetric indices MCV (P=0.002) and MCH (P=0.009) were lower than the control group, especially when compared to the group using LLLT 120h after radiotherapy (LLG). White blood cell counts were lower in the groups with radiotherapy and immediate use of LLLT (ILG) (P=0.011), mainly at the expense of lymphocytes (P=0.002). Conclusion: The results suggest a potential systemic effect of LLLT, especially on circulating red blood cell counts, regardless of their time of immediate or late use of radiotherapy. ِDOI: 10.34172/jlms.2021.45